Integrasi Nilai Teologi Islam dalam Kurikulum Pendidikan Islam Modern - Mas Dodi; Rusmal Kahvi; Irvan Trisno Susandi; Karyanto Karyanto; Suharyati Suharyati; Siti Uswatun Khasanah (SAP (Susunan Artikel Pendidikan), 2026)
Theology of Kalam plays a crucial role in shaping students' understanding of Islamic faith in a rational, critical, and contextual manner. In an era marked by technological advancements, social change, and diverse religious thought, the study of Kalam is not only directed at mastering theological concepts, but also at character building, strengthening faith, and students' ability to face the challenges of modern life. The integration of Islamic theological values ​​into the curriculum is achieved by connecting material on faith, the thoughts of Islamic scholars, and the values ​​of monotheism with the realities of students' lives. This study aims to analyze the integration of Islamic theological values ​​in the modern Islamic Education curriculum, specifically in the study of Kalam at Madrasah Aliyah An Nur Bekasi. Kalam plays a crucial role in shaping students' understanding of Islamic faith in a rational and critical manner, while simultaneously fostering a religious attitude that is adaptive to current developments. The research method used was descriptive qualitative research using a case study technique. Data were collected through observations of Kalam lessons, interviews with teachers and students, and analysis of curriculum documents and syllabi. The research results show that the integration of Islamic theological values ​​into the curriculum can strengthen students' Islamic identity and enhance their ability to understand Islamic teachings critically, relevantly, and contextually in modern life